Working and Resting Period based on Inclination, Loads, and Lift Methods on Manual Material Handling in Mining Environment - Eko Nurmianto1 , Udisubakti Ciptomulyono2 , Suparno3 , Sudiyono Kromodihardjo4 , Hari Setijono5 , Nu (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study assessed working period and resting period in handling return roll (RR) in laboratory. Deliveriesof a RR involve a shoulder/elbow-mode of carriage. Workers usually prefer the Carry On Shoulder (COS)(Gendong), or Carry On Elbow (COE) (Manggul) modes. The objective of the research are to measureWorking Period (WP) and Resting Period (RP) that converted into heart rate (HR) and oxygen uptake(VO2). Eight healthy male subjects performed shoulder/elbow-mode carrying. The type of research was aexperimental study. Lifting with the shoulder method feels lighter and takes distance much longer. The restperiod for the shoulder method has shorter rest periods because the work is lighter while carrying a longerrest period based on ANOVA test on the effect of inclination, load and lifting methods on Working andResting Periods.